Anti-inflammatory activity and chemical constituents of red limestone - Thidarat Duangyod; Narawadee Rujanapan; Sorraya Champakam; Rawiwan Charoensup (Wolters Kluwer Medknow Publications, 2021)
Red limestone is a mixture of turmeric (Curcuma longa L.) powder and limestone which is made from burning shells at high temperature. The yellow mixture turns to red color or deep orange because of the reaction between turmeric and calcium carbonate in limestone. Red limestone is traditionally used to treat many diseases such as abscess, cut wound and insect bite. The purpose of this study was to investigate anti-inflammatory activity and chemical constituents of red limestone. The chemical analysis of red limestone extract by liquid chromatography with tandem mass spectrometry revealed that red limestone consisted of alpha-turmerone and curcumanolide B as major components. These compounds were related with the chemical constituents in C. longa extract which is a main ingredient of red limestone. However, curcuminoids were not detected in red limestone extract. Cytotoxicity of red limestone extract was investigated. Macrophage cell lines (RAW 264.7) and human keratinocyte cell lines (HaCaT cells) were investigated cell viability using MTT assay. Red limestone extract was nontoxic to normal cells such as macrophage cells and human keratinocyte cells. Moreover, the inflammatory activity was detected nitric oxide (NO) secretion in RAW 264.7 cells. The result showed that the extracts inhibited NO in dose-dependent manner and IC50 was found to be 102.42 μg/ml. It suggested that red limestone extract had a potential for anti-inflammatory activity.